Words and music in the middle ages: song, narrative, dance and drama 1050-1350 - Stevens, John (Cambridge Cambridge University Press, 1986)
This book examines the relation of words and music in England and France during the three centuries following the Norman Conquest. The basic material of the study includes the chansons of the troubadours and trouvères and the varied Latin songs of the period. In addition to these 'lyric' forms, the author discusses the relations of music and poetry in dance-song, in narrative and in the ecclesiastical drama. Professor Stevens examines the ready-made, often unconscious, and misleading assumptions we bring to the study and performance of early music. In particular he affirms the importance of Number, in more than one sense, as a clue to the 'aesthetic' of the greater part of repertoire, to the relation of words and melody. and to the baffling problem of their rhythmic interpretation. This is the first wide-ranging study of words and music in this period in any language. It will be essential reading for scholars of the music and the literature of medieval Europe and will provide a basic and comprehensive introduction to the repertoire for students.